Multiaxial fatigue of additive manufactured metals: Performance, analysis, and applications - Fatemi, A.; Molaei, R.; Phan, N. (International journal of fatigue, 2020)
•Multiaxial fatigue of powder bed fusion additive manufactured metals.•Surface finish, defects, and heat treatment effects on multiaxial fatigue of AM metals.•Cyclic deformation and damage mechanism in multiaxial fatigue of AM metals.•Effects of notches and variable amplitude loading in multiaxial fatigue of AM metals. Additive manufacturing (AM) has recently gained much interest from researchers and practitioners in a wide range of industries due to the many advantages it offers, as compared to the traditional subtractive manufacturing methods. Some of distinguishing features of AM, as compared to traditional subtractive manufacturing methods, include surface roughness, porosity and lack of fusion defects, residual stresses due to the thermal history of the part during the fabrication process, and anisotropy of the properties. Considering the fact that the state of stress at fatigue critical locations is often multiaxial and many of the distinguishing features of AM metals are directional, the subject of multiaxial fatigue presents an important study area for a better understanding of their fatigue performance. This paper presents an overview of the aforementioned issues using recent data generated with AM Ti-6Al-4V and 17–4 PH specimens made by two different laser-beam powder bed fusion (LB-PBF) machines and subjected to axial, torsion, and combined in-phase as well as out-of-phase axial-torsion loadings. The role of fabrication induced defects, surface roughness, and residual stresses, in addition to post fabrication heat treatment processes are discussed with implications on multiaxial fatigue performance. Important topics to multiaxial fatigue are considered. These include cyclic deformation, damage mechanism and cracking behavior, as well as damage quantification and representation for data correlations and life estimation under different stress states. The effects of some other important issues to multiaxial fatigue performance of AM metals at the component or structure level, such as mechanical notches and variable amplitude loading, are also briefly discussed.